Interparental Relationship Sensitivity Leads to Adolescent Internalizing Problems: Different Genotypes, Different Pathways. Issue 2 (April 2015) - Schlomer, Gabriel L.; Fosco, Gregory M.; Cleveland, H. H.; Vandenbergh, David J.; Feinberg, Mark E.
<x xml:space="preserve">Abstract</x> Several studies have established that child interparental conflict evaluations link parent relationship functioning and adolescent adjustment. Using differential susceptibility theory and its vantage sensitivity complement as their framework, the authors examined differences between adolescents who vary in the DRD4 7 repeat genotype (i.e., 7+ vs. 7−) in how both interparental conflict and positivity affect adolescents' evaluations of interparental conflict (i.e., threat appraisals) and how these evaluations affect internalizing problems. Results from longitudinal multiple‐group path models using PROSPER data (N = 452) supported the hypothesis that threat appraisals for 7+ adolescents would be more affected by perceptions of interparental positivity compared to 7− adolescents; however, threat appraisals for 7+ adolescents were also less affected by interparental conflict. Among 7− adolescents, interparental conflict perceptions were associated with higher threat appraisals, and no association was found for perceptions of positivity. For adolescents of both genotypes, higher threat was associated with greater internalizing problems.